(In)visibility and the exercise of power: a genealogy of the politics of drag spectacles in a small city in South Africa,Invisibility and the exercise of power - Marx, Jacqueline Greer (Rhodes University, Faculty of Humanities, Department of Psychology, 2011)
This study investigates the politics of homosexual visibility in dressing-up, cross-dressing and drag performances that take place in a small city in South Africa over a period of sixty years, beginning in the 1950s and the inception of apartheid policy, through the socio-political changes in the 1990s to the 21st century post-apartheid context. The study draws on Butler's notion of performative resistance and adopts a Foucauldian genealogy to examine the conditions that make visibility possible and through which particular representations of homosexuality are articulated and read, or remain unread or misread. Information about dressing-up, cross-dressing and drag performance was obtained in interviews, from documentary evidence, and from audio-visual recordings of drag shows and gay and lesbian beauty pageant competitions. Semiotics and a Foucauldian approach to analysing discourse were used to interpret the written, spoken, and visual texts. In this study I argue that the state prohibition of homosexuality during apartheid meant that people could not admit to knowing about it, and this 'not knowing' provided a cover for homosexual behaviour in public. At this time, the threat of being identified was associated with police raids on private parties. In the 1990s, homosexual visibility was more viable than it had been in the past. However, the strategies that were adopted to negotiate public visibility at this time were tailored to appease normative sentiments rather than challenge them. I argue that, historically, race and gender have played a role in diminishing and exacerbating homosexual visibility and its politics. Addressing the potential for harm that is associated with homosexual visibility in the 21st century post-apartheid context, this study considers the circumstances in which invisibility is desirable.
Keywords: Female impersonators -- Research -- South Africa; Male impersonators -- Research -- South Africa; Apartheid -- South Africa -- Psychological aspects